Correction: Rewritable full-color computer-generated holograms based on color-selective diffractive optical components including phase-change materials. Issue 47 (23rd November 2018) - Hwang, Chi-Young; Kim, Gi Heon; Yang, Jong-Heon; Hwang, Chi-Sun; Cho, Seong M.; Lee, Won-Jae; Pi, Jae-Eun; Choi, Ji Hun; Choi, Kyunghee; Kim, Hee-Ok; Lee, Seung-Yeol; Kim, Yong-Hae
Abstract : Correction for 'Rewritable full-color computer-generated holograms based on color-selective diffractive optical components including phase-change materials' by Chi-Young Hwang et al., Nanoscale, 2018, DOI: 10.1039/c8nr04471f.